Return of the Padawan - Brown, Jeffrey, 1975-; Lucas, George, 1945- (Gosford, NSW : Scholastic Australia, 2014)
After surviving his first year at Jedi Academy, Roan Novachez thought his second year would be a breeze. This year, Roan will have to face alien poetry tests, menacing robots, food fights, flight simulation class, online bullies, more lightsaber duels, and worst of all ... a girl who is mad at him.
For children.
Keywords: Lucas, George, -- 1945- -- Comic books, strips, etc; Life on other planets -- Comic books, strips, etc; Star wars -- Comic books, strips, etc; Science fiction -- Comic books, strips, etc; Children's stories; Graphic novels